Exploring the Structural Competition between the Black and the Yellow Phase of CsPbI3 - Ioannis Deretzis; Corrado Bongiorno; Giovanni Mannino; Emanuele Smecca; Salvatore Sanzaro; Salvatore Valastro; Giuseppe Fisicaro; Antonino La Magna; Alessandra Alberti (Nanomaterials, 2021)
The realization of stable inorganic perovskites is crucial to enable low-cost solution-processed photovoltaics. However, the main candidate material, CsPbI3, suffers from a spontaneous phase transition at room temperature towards a photo-inactive orthorhombic δ-phase (yellow phase). Here we used theoretical and experimental methods to study the structural and electronic features that determine the stability of the CsPbI3 perovskite. We argued that the two physical characteristics that favor the black perovskite phase at low temperatures are the strong spatial confinement in nanocrystalline structures and the level of electron doping in the material. Within this context, we discussed practical procedures for the realization of long-lasting inorganic lead halide perovskites.